2008
DOI: 10.3748/wjg.14.2625
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art of irritable bowel syndrome and inflammatory bowel disease research in 2008

Abstract: Irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD) are two of the leading causes of chronic intestinal conditions in the world. This issue of World Journal of Gastroenterology (WJG ) presents a series of papers from world experts who discuss the current knowledge and opinions on these important conditions. Although great strides have been made in the diagnosis, treatment and pathology of IBS and IBD; much has yet to be explained. The etiologies and risk factors of these multifactorial conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…The altered motility, visceral hypersensitivity, dysfunctional brain-gut interaction, low-grade mucosal inflammation, genetic factors, food allergies, and altered bowel microflora can give rise to the characteristic clinical symptoms of IBS (25). Some studies incited the psychosocial aspects of IBS and FD, revealed altered GI symptoms of rotating shift workers, as a part of a various symptoms (26). Furthermore, several studies have reported a higher prevalence of GI symptoms such as diarrhea, bloating, and heartburn among the rotating shift workers compared to daytime worker (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…The altered motility, visceral hypersensitivity, dysfunctional brain-gut interaction, low-grade mucosal inflammation, genetic factors, food allergies, and altered bowel microflora can give rise to the characteristic clinical symptoms of IBS (25). Some studies incited the psychosocial aspects of IBS and FD, revealed altered GI symptoms of rotating shift workers, as a part of a various symptoms (26). Furthermore, several studies have reported a higher prevalence of GI symptoms such as diarrhea, bloating, and heartburn among the rotating shift workers compared to daytime worker (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of IBS ranges from 3%–25% of adults and causes much morbidity and cost in terms of lost time at work and drain on health resources 86. Because the symptoms of IBS are common to a number of other GI conditions, IBS was long considered a “diagnosis of exclusion”, leading to excessive testing of patients with characteristic symptoms.…”
Section: The Role Of Pcps In Early Diagnosis and Management Of Patienmentioning
confidence: 99%
“…The direct and indirect healthcare costs related to IBS in the United States have been steadily increasing and amounted to 1.35 billion dollars in 2003 [ 6 ]. The worldwide health costs associated with IBS are estimated to exceed 200 billion dollars [ 7 ].…”
Section: Introductionmentioning
confidence: 99%